Optimizing Human Resources Management For Higher Education in the Era of Implementing an Independent Curriculum in Indonesia - Jenita Jenita; Ratna Nurdiana; I Made Gede Ariestova Kurniawan; Darnilawati; Diana Triwardhani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This study aimed to analze how Suska Riau state Islamic university optimizes managing its college human resources in implementing the independent curriculum. Many studies have been carried out in developing higher education human resources, but they are related to something other than the independent curriculum. We obtained meaningful input and extracted information from several related literatures through semi-structured interviews with teaching staff and university leaders. As for the process, other than interviews, we obtained data through an electronic search on several scientific publications discussing higher education human resources issues. After processing the data and discussing it, we can conclude that the efforts of Islamic state universities have taken several strategies to optimize their HR management; among others, they are taking digitalization and automation systems as well as developing learning all these things in order to make their campuses leading in the area. Thus, this finding will become a reference for adding different study areas. Keywords: Human Resource Management, Optimizing Human Resources, Curriculum Indonesia